The formation of a nation state through history education in Malaysia: A literature review - Shapiza Sharif (ResearchGate, 2023)
This article aims to identify and analyse previous studies on nation-state education in History education in Malaysia. Issues commonly raised are related to the concept of nation-state education and its relationship with History education. In general, there have been many nation-state education efforts implemented to improve Malaysians’ understanding of the concept to boost their sense of identity, especially among Malaysian youths in educational institutions. Yet, there are still features and elements that are hindering efforts to develop a nation state for this country. Hence, to analyse the concerns identified in the literature review, a qualitative approach based on document analysis of secondary sources was used for data analysis. The outcomes of this analysis will be utilised to map out future research on nation-state education, with a focus on history teaching.